Land Acquisition Analysis for Public Interest in Sorong Special Economic Zone (KEK) Southwest Papua Province - Madaul, rahful; Ummi Hanifah M.; Hilmi Hilmansyah (Jurnal Dialektika: Jurnal Ilmu Sosial, 2024)
The potential of the Sorong Special Economic Zone (KEK Sorong) extends beyond merely creating jobs and attracting investment. It also opens doors for infrastructure development, improved connectivity, and enhanced human resource quality in the region. By integrating key sectors such as fisheries, agro-industry, and logistics, KEK Sorong is expected to establish a sustainable economic ecosystem and bring positive impacts to the local community. Land acquisition in KEK Sorong is crucial to address these disparities. This research employs qualitative methods. Data analysis in this research is qualitative analysis. The findings of this study are: (a) Land ownership in KEK Sorong includes four existing business entities that were established before it was designated as a KEK, namely PT. Semen Indonesia (Persero) Tbk, PT. Henrison Inti Persada, PT. Perahu Catamaran Papua, and PT. Satu Suku Pertanian; (b) The land area planned, based on the cumulative results of delineation of land ownership maps, the planned location for land acquisition in the Sorong Special Economic Zone (KEK) covers 2,205,000 m² or 208.5 Ha, which is under the customary land ownership of the Kami Clan; (c) The land acquisition location for KEK Sorong in Southwest Papua Province, based on an overlay with the Sorong Regency Spatial Plan (RTRW), shows that most of KEK Sorong is designated as an industrial area with a total area of 291.7 Ha; (d) Land use in KEK Sorong includes utilization for plant growth and corporate activities, as well as a port; (e) The social impact of land acquisition activities includes both social impacts and individual and family impacts.